Implementation of Quiziz Learning Media as a Diagnostic Assessment in Indonesian Language Learning for Class XI Students Of SMA Negeri 4 Palembang - Houtman Houtman; Bella Aguslistiana; Indah Dian Yusmalia; Muhammad Bakti Karuniawan; Nadea Ayu Irpanis; Nurhayati Nurhayati (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
This research aims to explore the implementation of Quizizz learning media as a diagnostic assessment tool for class XI students at SMA Negeri 4 Palembang. The research method used is classroom action research which involves active participation from students and teachers. Data was collected through observation, interviews, and analysis of Quizizz evaluation results. The research results show that using Quizizz as a diagnostic assessment tool can increase student engagement in learning and provide a more accurate picture of their understanding of the lesson material. These findings highlight the potential of Quizizz in increasing the effectiveness of the learning process in class XI SMA Negeri 4 Palembang. The practical and pedagogical implications of this research are discussed to enrich and expand learning practices in schools understanding of the use of learning media in the context of diagnostic assessment. understanding of the use of learning media in the context of diagnostic assessment.